STAT4 expression and activation is increased during mitosis in vitro and in vivo in skin‐ and mucosa‐derived cell types: implications in neoplastic and inflammatory skin diseases. (10th August 2017) - Ferreli, C.; Lai, C.; August, S.; Buggy, Y.; Kumar, P.; Brownlow, N.; Parker, P.; Friedmann, P.S.; Ardern‐Jones, M.; Pickard, C.; Healy, E.
Abstract: Background: The signal transducer and activator of transcription‐4 (STAT4/Stat4) is a transcription factor known to convey signals from interleukin‐12, interleukin‐23, and interferon‐alpha/beta to the nucleus, resulting in activation of dendritic cells, T‐helper cell differentiation and production of interferon‐gamma. Objective: To demonstrate a novel role for STAT4 in cell mitosis. Results: Phosphoserine STAT4 (pSerSTAT4) is increased in cells undergoing mitosis and is distributed throughout the cytoplasm during this stage of the cell cycle, whilst phosphotyrosine STAT4 (pTyrSTAT4) is confined to the chromosomal compartment. This distinct pattern of pSerSTAT4 during mitosis is seen in vitro in human keratinocytes and in other cell types. This is also present in vivo in cells undergoing mitosis in normal skin, psoriasis and squamous cell carcinoma. Inhibition of STAT4 phosphorylation by lisofylline and depletion of STAT4 by RNA interference results in a delay in progression of mitosis and leads to a reduction in cells completing cytokinesis. Conclusion: Our data demonstrate that STAT4 plays a role in enabling the normal and timely division of cells undergoing mitosis.